Evaluating the Corporate Social Responsibility Disclosure of Nigeria’s Most Profitable Companies - Abass Olabode Samuel; Umaru Zubairu; Bilkisu Abubakar (Universitas Airlangga, 2020)
This study evaluated Corporate Social Responsibility (CSR) disclosure in the most profitable companies in Nigeria, a review was carried out on the annual reports and websites of the five most profitable companies in Nigeria according to the market cap list 2018. This research focused on the quantity and quality of CSR disclosures, provided by these companies. The method of analysis used was content analysis. The result of this study revealed that from the three dimensions constituting Community disclosure, Environmental disclosure and Human Resource disclosure, Community disclosure was the most disclosed dimension from the top profitable companies in Nigeria. Findings revealed that these companies disclosed a lot about the different CSR activities they had undertaken within the span of one year, but the quality of these disclosures were relatively low. CSR disclosure should be encouraged by the Nigerian government by publicly recognizing companies who disclose CSR activity, this will motivate other companies to practice and disclose CSR.